2022
DOI: 10.4209/aaqr.210337
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation Strategy for Proper IAQ in Existing Nurseries Buildings - Lesson Learned from the Research during COVID-19 Pandemic

Abstract: During the COVID-19 pandemic, many recommendations were made in the field of limiting the transmission of the SARS-CoV-2 virus, from which we can learn a lesson for determining ventilation strategies in strategic types of buildings (those whose closure during a pandemic is harmful to the economy, e.g. nurseries). The research was aimed at identifying recommendations in the field of ventilation and proposing a solution that would be applicable in existing buildings intended for the care of small children, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…A number of studies have indicated that there is still large uncertainty in accurately describing indoor aerosol deposition (e.g., (Diapouli et al, 2013)). Factors including ventilation type (Izadyar and Miller, 2022;Ratajczak, 2022;Zhao and Wu, 2009), forced-air stirring vs. calm, unstirred rooms (Schnell et al, 2006), furnishings (Abadie et al, 2001;Thatcher et al, 2002;Thatcher and Nazaroff, 1997), room or building geometry, intrusion of outside air to the…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A number of studies have indicated that there is still large uncertainty in accurately describing indoor aerosol deposition (e.g., (Diapouli et al, 2013)). Factors including ventilation type (Izadyar and Miller, 2022;Ratajczak, 2022;Zhao and Wu, 2009), forced-air stirring vs. calm, unstirred rooms (Schnell et al, 2006), furnishings (Abadie et al, 2001;Thatcher et al, 2002;Thatcher and Nazaroff, 1997), room or building geometry, intrusion of outside air to the…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Practically, mechanical systems or opening doors and windows can both provide adequate ventilation [ 30 , 31 ]. The main advantage of natural ventilation is that it is a theoretically cheap and easy-to-use solution (opening the windows sufficiently), but it also disturbs the thermal regulation of the room [ 25 ]. Relatively, the implementation of mechanical ventilation is considered the best strategy to ensure adequate air quality, as it can be a additional, precise adjunct to the control procedures [ 30 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other empirical studies on IAQ and COVID-19, the similarities between them are that they all explore ways of improving IAQ to reduce the spread of COVID-19 [ 13 , 14 , 23 , 24 , 25 , 26 , 27 , 29 ], however, the biggest difference is the design and choice of research methods. For example, most of the studies have used instrumental monitoring [ 13 , 14 , 21 , 22 , 23 , 24 , 25 , 28 , 29 ], and a few have used literature reviews [ 20 ] or participant observation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Creating a good indoor environment is particularly important for human health (Zhang et al, 2020). At present, ventilation systems have been widely used to control indoor particle exposure (Zhou et al, 2021a;Ratajczak et al, 2022). However, outbreaks of the coronavirus disease show that indoor environment control still face many new challenges (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%